Process and position power: a social relational research agenda about state power in negotiations. Issue 12 (2nd December 2022) - Lovato, Marianna; Maurer, Heidi
ABSTRACT: Relational approaches bear a distinct added value for the study of the EU and international negotiations. In this research note we advocate for the combination of social network analysis with practice theory to better capture social relational forms of state power. We introduce the concepts of position and process power to develop an analytical framework that conceptualizes negotiations as dynamic interactions between the two. We contend that negotiation outcomes rest on a country's ability to shape subsequent network configurations based on its initial network position and its competent performance of practices. Among other things, our framework offers a nuanced understanding of the formation and role of coalition groupings as well as the forms of social relational power that can emerge among states. As we argue, states can both 'be' (due to exogenous and pre-existing factors) and 'become' powerful (thanks to the social dynamics unique to each negotiation).